2013
DOI: 10.1038/eye.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic vitreomacular traction and macular hole: a comprehensive review of pathophysiology, diagnosis, and treatment

Abstract: Posterior vitreous detachment (PVD) is a common phenomenon in the aging eye. However, this may be complicated by persistent symptomatic vitreomacular adhesions that exert tractional forces on the macula (vitreomacular traction; VMT). VMT itself may be associated with epiretinal membrane formation and the development of idiopathic macular holes (IMH). Such pathologies may cause visual disturbances, including metamorphopsia, photopsia, blurred vision, and decreased visual acuity, which impact an individual's qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
1
23

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 148 publications
(265 reference statements)
2
168
1
23
Order By: Relevance
“…Various ocular structures are affected by aging, such as the macula, the functional center of the retina responsible for precise central vision. Idiopathic epiretinal membrane (iEMR) and macular hole (MH) are the major vision‐threatening vitreoretinal interface diseases that affect millions of aging people globally, making these conditions an important public health issue (Steel & Lotery, 2013). iERM is characterized by the growth of fibrocellular tissue along the inner surface of the retina (Snead, James, & Snead, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various ocular structures are affected by aging, such as the macula, the functional center of the retina responsible for precise central vision. Idiopathic epiretinal membrane (iEMR) and macular hole (MH) are the major vision‐threatening vitreoretinal interface diseases that affect millions of aging people globally, making these conditions an important public health issue (Steel & Lotery, 2013). iERM is characterized by the growth of fibrocellular tissue along the inner surface of the retina (Snead, James, & Snead, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This would be in keeping with our understanding of the pathogenesis of VMT and macular hole formation. 6 A potential strength of this study is the use of a very pragmatic and easy grading system for VMT features on OCT scan. This study revealed a potential cut-off when cysts are present near the fovea on OCT scans.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] This gives rise to a hyper-reflective line anterior to the retinal surface visible on optical coherence tomography (OCT) scans, which is either not associated with any structural changes of the retinal parenchyma, so-called vitreomacular Adhesion (VMA) or VMT, where some effect of traction is visible. [6][7][8] The ease with which VMT can be diagnosed using OCT has enabled accurate selection of patients for therapeutic interventions with surgery or pharmacological vitreolysis and also enabled detailed studies on classification, staging, and further understanding of the natural history of VMT. [9][10][11][12][13] Although it has been widely recognised that VMT can occur in isolation or in association with common diseases of the macula such as diabetic macular oedema, retinal vein occlusion, posterior uveitis, and age-related macular degeneration, [14][15][16] there have been no published data on the incidence of VMT in the general population or in the population of patients who have been referred to the hospital eye service.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Even if the present report is on few patients, our limited experience Table 3 Surgical procedure performed with a three-port pars plana vitrectomy under retrobulbar anaesthesia by the same surgeon (EMV), according to the following schedule and guidelines (the Declaration of Helsinki, Institutional Review Board, and informed consent was obtained from all subjects before enrolment)…”
Section: Discussionmentioning
confidence: 99%